Mengubah Ide Menjadi Peluang Bisnis - Apila Nabila Sari; Alya Zaharatul Hasanah; Veta Lidya Delimah Pasaribu (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This Community Service Activity (PKM) aims to provide understanding and knowledge to students of SMA Pelita Bangsa regarding how to transform ideas into profitable business opportunities. In the current digital era, entrepreneurial ability has become one of the important skills that the younger generation must possess to face global competition. This activity uses a qualitative approach with participatory action research (PAR) methods including observation, Focus Group Discussion (FGD), in-depth interviews, SWOT analysis, entrepreneurship workshops, and implementation of materials and interactive question-and-answer sessions. The results showed that students of SMA Pelita Bangsa already have potential and experience in developing business ideas, such as fried chicken business, spare parts sales, and e-commerce utilization. The main challenges faced include similar businesses, intense competition, and limited capital. However, there are great opportunities to optimize environmental support, cooperation with various parties, and technology utilization. Recommended strategies include utilizing e-commerce, using social media for promotion, and implementing technology-based information systems. This activity makes a positive contribution to increasing students' entrepreneurial spirit and providing practical knowledge to develop businesses with limited capital.